2022
DOI: 10.3390/healthcare10061007
|View full text |Cite
|
Sign up to set email alerts
|

Care Dependency of Hospitalized Stroke Patients Based on Family Caregivers’ and Nurses’ Assessments: A Comparative Study

Abstract: Stroke impacts care dependency, and thus the patient needs home care after suffering a stroke. This study was carried out to investigate similarities and differences between the assessments made by family caregivers and nurses regarding the care dependency level of stroke patients in Indonesian hospitals. This study was a comparative study of the care dependency of stroke patients. Data were collected on the stroke wards on the day of admission using the Care Dependency Scale (CDS). The sample consisted of 118… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In this study, we found that the teach-back method is an easy-to-understand, safe, and effective method of health education (13). Normative family continuity care helps patients and their families to receive targeted healthcare guidance and plays an important role in promoting recovery from disease (17,18). For family caregivers, the results of this study showed that there were significant effects of time, group, and the time-group interaction on total caring ability scores and scores on each of the four dimensions of caring abilities.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, we found that the teach-back method is an easy-to-understand, safe, and effective method of health education (13). Normative family continuity care helps patients and their families to receive targeted healthcare guidance and plays an important role in promoting recovery from disease (17,18). For family caregivers, the results of this study showed that there were significant effects of time, group, and the time-group interaction on total caring ability scores and scores on each of the four dimensions of caring abilities.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we found that the teach-back method is an easy-to-understand, safe, and effective method of health education ( 13 ). Normative family continuity care helps patients and their families to receive targeted healthcare guidance and plays an important role in promoting recovery from disease ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Singapore noted that by adult children taking turns in care, pooling resources, and distributive support (determining which part of care each person is competent in), patients avoid to some extent the influence brought about by medical decision-making activities and become less dependent ( Tyagi et al, 2021 ); on the other hand, it has been noted that the cultural context influences the tendency for children to care for their parents, which has an impact on the children’s own lives and work. In this regard, parents feel guilty and try to reduce their needs to ease the burden of their children ( Liu et al, 2020b ; Liu, 2021 ; Nursiswati et al, 2022 ), resulting in an apparent “low dependency”.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, for patients with severe stroke and concurrent mobility impairment, cognitive impairment and other neurological deficits, being an adult child shows a more active role in monitoring changes in the patient's condition, improving communication with the health care team and helping the patient in making medical decisions during the early stages of the illness (van Ryn et al, 2011;Shin et al, 2013;Isenberg et al, 2018;Fenton et al, 2022).A study in Singapore noted that by adult children taking turns in care, pooling resources, and distributive support (determining which part of care each person is competent in), patients avoid to some extent the influence brought about by medical decision-making activities and become less dependent (Tyagi et al, 2021); on the other hand, it has been noted that the cultural context influences the tendency for children to care for their parents, which has an impact on the children's own lives and work. In this regard, parents feel guilty and try to reduce their needs to ease the burden of their children (Liu et al, 2020b;Liu, 2021;Nursiswati et al, 2022), resulting in an apparent "low dependency".…”
Section: Caregivermentioning
confidence: 99%
“…If stroke pilots had visited patients at home, other requirements that patients did not actively mention by themselves could have been more obvious. In addition, further topics might have been generated by investigating the caregiver’s or professional’s opinion on the patients’ needs, which has been performed in earlier approaches [ 43 , 44 ]. Third, because of the monocentric and, in proper meaning, non-interventional study design, the sample size is relatively small, and a control group is lacking, which limits the generalizability of the study findings.…”
Section: Discussionmentioning
confidence: 99%